Therapeutic Pretargeting with Gold Nanoparticles as Drug Candidates for Boron Neutron Capture Therapy. (23rd September 2020) - Feiner, Irene V. J.; Pulagam, Krishna R.; Gómez‐Vallejo, Vanessa; Zamacola, Kepa; Baz, Zuriñe; Caffarel, María M.; Lawrie, Charles H.; Ruiz‐de‐Angulo, Ane; Carril, Mónica; Llop, Jordi
Abstract: Boron neutron capture therapy (BNCT) is a binary approach for cancer treatment in which boron‐10 atoms and thermal neutrons need to colocalize to become effective. Recent research in the development of BNCT drug candidates focuses increasingly on nanomaterials, with the advantages of high boron loadings and passive targeting due to the enhanced permeability and retention (EPR) effect. The use of small boron‐rich gold nanoparticles (AuNPs) in combination with a pretargeting approach is proposed. Small sized polyethylene glycol–stabilized AuNPs (core size 4.1 ± 1.5 nm),  are synthesized and functionalized with thiolated cobalt bis (dicarbollide) and tetrazine. To enable in vivo tracking of the AuNPs by positron emission tomography (PET), the core is doped with [ 64 Cu]CuCl2 . For the pretargeting approach, the monoclonal antibody Trastuzumab is functionalized with trans ‐cyclooctene‐ N ‐hydroxysuccinimide ester. After proving in vitro occurrence of the antibody conjugation onto the AuNPs by click reaction and the low toxicity of the AuNPs, the boron delivery system is evaluated in vivo using breast cancer xenograft bearing mice and PET imaging. Tumor uptake due to the EPR effect can be witnessed with ≈5% injected dose (ID) cm −3 at 24 h postinjection, but with slower clearance than expected. Therefore, no increased retention can be observed using the pretargeting strategy. Abstract : Small‐sized polyethylene glycol–stabilized gold nanoparticles functionalized with cobalt bis (dicarbollide) and tetrazine are radiolabeled with copper‐64 to enable in vivo tracking using positron emission tomography and evaluated in a mouse model of breast cancer under a pretargeting approach. Tumor uptake is observed, although slow clearance prevents increased retention under pretargeting conditions.